Three Novel and One Potential Hotspot CPT1A Variants in Chinese Patients With Carnitine Palmitoyltransferase 1A Deficiency - Zhang, Weifeng; Chen, Yanru; Lin, Chunmei; Peng, Weilin; Fu, Qingliu; Lin, Yiming (Frontiers in Pediatrics, 2021)
Carnitine palmitoyltransferase 1A (CPT1A) deficiency is an inherited disorder of mitochondrial fatty acid β-oxidation that impairs fasting ketogenesis and gluconeogenesis in the liver. Few studies implementing newborn screening (NBS) for CPT1A deficiency in the Chinese population have been reported. This study aimed to determine the biochemical, clinical, and genetic characteristics of patients with CPT1A deficiency in China. A total of 204,777 newborns were screened using tandem mass spectrometry at Quanzhou Maternity and Children’s Hospital between January 2017 and December 2018. Newborns with elevated C0 levels were recruited, and suspected patients were subjected to further genetic analysis. Additionally, all Chinese patients genetically diagnosed with CPT1A deficiency were reviewed and included in the study. Among the 204,777 screened newborns, two patients were diagnosed with CPT1A deficiency; thus, the estimated incidence in the selected population was 1:102,388. In addition to the two patients newly diagnosed with CPT1A deficiency, we included in our cohort ten Chinese patients who were previously diagnosed. Five of these twelve patients were diagnosed via NBS. All patients exhibited elevated C0 and/or C0/(C16+C18) ratios. No clinical symptoms were observed in the five patients diagnosed via NBS, while all seven patients presented with clinical symptoms, including fever, cough, vomiting, diarrhea, and seizures. Eighteen distinct CPT1A variants were identified, fifteen of which have been previously reported. The three novel variants were c.272T>C (p.L91P), c.734G>A (p.R245Q), and c.1336G>A (p.G446S). In silico analysis suggested that all three novel variants were potentially pathogenic. The most common variant was c.2201T>C (p.F734S), with an allelic frequency of 16.67% (4/24). Our findings demonstrated that NBS for CPT1A deficiency is beneficial. The three novel variants expand the mutational spectrum of CPT1A in the Chinese population, and c.2201T>C (p.F734S) may be a potential hotspot CPT1A mutation.